Australian inpatient cancer rehabilitation, as seen by patients receiving care, pre‐ and post‐intervention. (30th July 2019) - Reynolds, Najwa; Cole, Andrew M.; Walmsley, Bruce; Poulos, Christopher J.
Abstract: Objective: Rehabilitation is increasingly recognised as effective in addressing impairment and functional disability after cancer treatment. Few studies have investigated the lived positive and negative experiences of cancer patients receiving rehabilitation. Method: Semi‐structured in‐depth interviews were conducted with 22 inpatient volunteers, at their admission and discharge from a subacute hospital rehabilitation unit. We heard narratives of their experiences and their individual goals in our programmes, seeking to make positive and negative subjective interpretations of these. We undertook Interpretative Phenomenological Analysis (IPA) of interviews. Results: Patients described an immense array of personal challenges, including coping with and adapting to functional losses, whilst assimilating the reality that life might not continue as before. They were often living and rehabilitating after the residual effects of cancer treatments, whilst facing new challenges that threatened their quality of life. Although rehabilitation usually improved patients' functional abilities, many still increasingly needed to depend on others in daily life. Conclusion: Understanding the narrative of these experiences provides a unique consumer evaluation of an inpatient cancer rehabilitation service. Individuals described a healing environment, where they received multiple therapies and set goals to improve daily living function, as they continued along their personal cancer trajectories.